2005
DOI: 10.1111/j.1751-1097.2005.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Defenses and DNA Damage Induced by UV‐A and UV‐B Radiation in the Crab Chasmagnathus granulata (Decapoda, Brachyura)

Abstract: The photoprotector role of pigment dispersion in the melanophores of the crab, Chasmagnathus granulata, against DNA and oxidative damages caused by UV‐A and UV‐B was investigated. Intact and eyestalkaless crabs were used. In eyestalkless crabs, the dorsal epidermis of the cephalothorax (dispersed melanophores) and the epidermis of pereiopods (aggregated melanophores) were analyzed. Intact crabs showed only dispersed melanophores in the two epidermis. Antioxidant enzymes activity and lipoperoxidation content we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Marine arthropods (i.e., crabs, lobsters, and shrimp) vary in their antioxidant defenses according to their level of aerobic metabolism, exposure to chronically cold environments, or exposure to UVR (111)(112)(113). Surprisingly, marine arthropods lack Cu/Zn SOD (114,115).…”
Section: Oxidative Stress In Marine Organismsmentioning
confidence: 99%
“…Marine arthropods (i.e., crabs, lobsters, and shrimp) vary in their antioxidant defenses according to their level of aerobic metabolism, exposure to chronically cold environments, or exposure to UVR (111)(112)(113). Surprisingly, marine arthropods lack Cu/Zn SOD (114,115).…”
Section: Oxidative Stress In Marine Organismsmentioning
confidence: 99%
“…Therefore, the purpose of this study has been, first, to confirm apoptosis under the same conditions used previously with the TdT-mediated dUTP-biotin nick end-labeling (TUNEL) technique, and then to test, in the visual system of this same species, whether catalase, Bax, and p53 expression (by using immunohistochemistry) and levels (through immunoblotting) are affected by the same high dose of UVB and UVC radiation used previously. A remark should be added here regarding the focus of this study: even though the effects caused by UVA and UVB have received more attention than those produced by UVC (Sanford et al 1996;Duncan et al 1997;Gouveia et al 2005), the latter should not be neglected, because, among other reasons, the study of UVC radiation may help us to understand some of the underlying mechanisms of UV-induced cell damage.…”
Section: Introductionmentioning
confidence: 96%
“…Patton et al (1999) also showed higher DNA damage in bovine retinal pigment epithelium cells (RPE) irradiated with UVB (0.012 J cm −2 ). At the highest dose of UVB (0.075 J cm −2 ), nuclei in the slides of the comet assay were not visible, suggesting that there may be a somatic effect of UVB radiation and the comet assay protocol, which may lead to cell destruction (Gouveia et al 2005). However, Patton et al (1999), utilizing higher doses of UVB (0.045 and 0.09 J cm −2 ), achieved to visualize nuclei and DNA damage in RPE cells.…”
Section: Highmentioning
confidence: 89%
“…While UVC is essentially completely absorbed by oxygen and is thus ecologically irrelevant, the longer UVB and UVA wave lengths ate relevant and can induce a variety of effects on many organisms. The deleterious effects of UVR range from molecular and tissue damage to population level Communicated by Wayne S. Gardner * José Henrique Muelbert docjhm@furg.br effects (Wake 1991;Kerr and McElroy 1993;Blaustein et al 1994;Bothwell et al 1994;Hofer and Mokri 2000;Ravanat et al 2001;Armstrong et al 2002) including damage to relevant biological molecules such as proteins, lipids, and DNA (Sinha and Hader 2002;Gouveia et al 2005).…”
Section: Introductionmentioning
confidence: 99%